A heart in a body in the world - Caletti, Deb (Simon Pulse, 2018)
Followed by Grandpa Ed in his RV and backed by her brother and friends, Annabelle, eighteen, runs from Seattle to Washington, D.C., becoming a reluctant activist as people connect her journey to her recent trauma.